Direct Transformation of Alkylarenes into N‐(Pyridine‐2‐yl)amides by C(sp3)–C(sp3) Bond Cleavage. Issue 41 (29th September 2020) - Zhou, Haipin; Liu, Yanpeng; Xia, Haidong; Xu, Jinyi; Wang, Tingfang; Xu, Shengtao
Abstract : C(sp 3 )–H bond functionalization and C(sp 3 )–C(sp 3 ) bond cleavage are very challenging transformations in chemistry. Herein, we report a mild and green methodology for the construction of N ‐(pyridine‐2‐yl)amides via tandem C(sp 3 )–H activation/C–C bond cleavage of alkylarenes. Various N ‐heterocyclic amides were directly synthesized from alkylarenes in water in moderate to good yields. Abstract : A mild and green methodology for the construction of N ‐(pyridine‐2‐yl)amides from alkylarenes and 2‐aminopyridine in one step was developed. Various alkylarenes were directly transformed into the corresponding N ‐(pyridine‐2‐yl)amides through tandem C(sp 3 )–H bond activation/oxidative cyclization/C–C bond cleavage.